Trading in Times of Crisis: Democratic Control over the EU’s Unilateral Trade Policy - Thomas Verellen (European Journal of Risk Regulation)
This article examines the democratic control over the European Union’s unilateral trade policy. It takes as a starting point how crises like COVID-19 and geopolitical tensions have led to the “weaponisation” of trade, making global commerce unpredictable. The EU has responded by modernising its trade instruments, such as anti-dumping measures and new regulations like the Anti-Coercion Instrument. However, these instruments often allow the European Commission to act without parliamentary approval, challenging democratic accountability. The article questions whether a democratic, yet effective, unilateral trade policy is possible for the EU. It reviews the processes behind the EU’s unilateral trade policy, critiques current legitimacy mechanisms and proposes reforms to enhance democratic oversight. Ultimately, it argues that a degree of democratisation of trade policy is feasible without Treaty changes, contributing to broader discussions on maintaining democratic control over executive actions in crises.